The Role of Muhammad Mustafa Al-A'zami in Responding to the Orientalist View of the Authenticity of Hadith - Fahmi Royhan; Tajul Arifin; Irwan Abdurrahman; Asim Ismail Kanaan; Muhammad Zheeva Al-Kasyaf (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This study explores the contribution of Muhammad Mustafa Azami in responding to Orientalist critiques of the authenticity of hadith as a primary source of Islamic teachings. In contemporary Islamic studies, hadith has often been the target of criticism, particularly by Western Orientalists such as Joseph Schacht, who argued that hadith was a fabrication by later Muslim scholars rather than originating from the Prophet Muhammad himself. Such views have undermined the authority of hadith and shifted its central role in Islamic epistemology. Azami, a renowned hadith scholar and academic, systematically refuted these claims through his seminal works, including Studies in Early Hadith Literature and On Schacht’s Origins of Muhammadan Jurisprudence. He challenged the Orientalist methodology and demonstrated that both the isnad (chain of transmission) and matn (content) of hadith were preserved and codified with rigorous scholarly discipline since the earliest generations of Islam. This research employs a qualitative approach using literature review methods to analyze Azami’s arguments. The findings reveal that Azami not only reaffirmed the authenticity of hadith but also strengthened its standing in global academic discourse. His contributions significantly defend the integrity of Islamic scholarly tradition and foster a more balanced dialogue between classical Islamic and contemporary Western approaches.